Implementasi Pengelolaan Manajemen Sumber Daya Manusia pada Tadika Brilliant BUDS Edukids Malaysia - Ananda, Runi; Hayati, Isra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The study aims to determine the implementation of human resource management at Tadika Brilliant Buds Edukids Malaysia in making efforts to improve the quality of education and the effectiveness of human resource management in the future. Aspects of human resource management at Tadika Brilliant Buds Edukids Malaysia include the recruitment process, selection, orientation, performance management, and compensation. The method used in this study is a descriptive approach that is included in the qualitative category. The data sources obtained consist of primary data, such as the results of interviews with respondents, as well as secondary data including research journals, books, and documentation. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that effective human resource management makes a significant contribution to improving the quality of education and child involvement. However, challenges such as limited resources must be overcome to achieve optimal results. Research can add valuable insight for Tadika managers in formulating better human resource management strategies to support the development of early childhood education.